Dinamika Sosio-Ekonomi Pedagang Santri dalam Mengembangkan Industri Kretek di Kudus, 1912-1930 - Muhamad Yusrul Hana (UIN Sumatera Utara Medan, 2018)
This paper explain about study on local history on the economic action of santri trader in kretek industry in Kudus 1912-1930. The early trading system of kretek cigarettes was dominated by santri trader until Chinese began producing kretek cigarettes as well, which causes significant profit decline for santri trader. It raised socio-economic tension between the two ethnic due to economic rivalry relations. In the middle of 1912, Chinese merchants started taking over kretek cigarettes market in Kudus. The rivalry matters turns out to be a competition and reach its peak on October 1918 when santri Kudus commence attacking and destroying homes and shops owned by chinese. The falling economic of Chinese, has made Nitisemito and H.M Muslich (Santri trader figure) motivated to maximize their ability in developing kretek cigarette trading system in Kudus. There are several main points that will be explained furthermore in this study. First, the depict of construction between santri traders and chinese merchants in Kudus, second, the effort of Nitisemito and H.M. Muslich in founding kretek cigarettes factory, third, understanding of sosio-economic patterns and economic action of santri trader in Kudus. The methode that be used in this study is historical research contains heuristic, criticism, interpretation, and historiography.Keywords: economic action, santri trader, kretek industry